2020
DOI: 10.3390/vehicles2020020
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Maximum Speed on the Power Density of Electromechanical Powertrains

Abstract: In order to achieve the European Commission’s ambitious climate targets by 2030, BEVs (Battery Electric Vehicles) manufacturers are faced with the challenge of producing more efficient and ecological products. The electromechanical powertrain plays a key role in the efficiency of BEVs, which is why the design parameters in the development phase of electromechanical powertrains must be chosen carefully. One of the central design parameters is the maximum speed of the electric machines and the gear ratio of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Increasing interest in such materials is also exemplified by recent patent applications, e.g., from Tesla [57,58]. The aspect of strength is introduced here due to the fact that there is a tendency in the automotive industry to increase electrical traction motor speed to allow for more compact designs, a trend which will raise the centrifugal forces acting on the rotors [59,60]. Beyond this, requirements regarding conductivity resemble those for radio filters and other electronic components as described above (see Figure 3).…”
Section: R Peer Review 5 Of 59mentioning
confidence: 99%
“…Increasing interest in such materials is also exemplified by recent patent applications, e.g., from Tesla [57,58]. The aspect of strength is introduced here due to the fact that there is a tendency in the automotive industry to increase electrical traction motor speed to allow for more compact designs, a trend which will raise the centrifugal forces acting on the rotors [59,60]. Beyond this, requirements regarding conductivity resemble those for radio filters and other electronic components as described above (see Figure 3).…”
Section: R Peer Review 5 Of 59mentioning
confidence: 99%
“…Scholar Schweigert D analyzed the maximum speed and power of the electromechanical power system based on motor transmission characteristics. It was found that increasing the maximum speed of the motor had a significant impact on enhancing the power of the electromechanical power system [15]. In the field of hybrid vehicles, Tang X. proposed a novel approach that combines vision technology with deep reinforcement intelligent control algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Yilmaz et al (2019b) also measured superlubricity in gears. Sedlmaier et al (2020) conducted experiments on a BEV test rig with the lubricants investigated by Yilmaz et al (2019a, b) and found a reduction of power losses of up to 74% compared to PAOs. Habchi et al (2011) carried out numerical investigations on the influence of the water content of glycerol on friction and film thickness in EHL contacts.…”
Section: Introductionmentioning
confidence: 99%